Effect of instrumentation using curettes, piezoelectric ultrasonic scaler and er,cr:Ysgg laser on the morphology and adhesion of blood components on root surfaces - A SEM study - Tsurumaki, Jackeline do Nascimento [UNESP]; Souto, Bráulio Henrique Marques [UNESP]; de Oliveira, Guilherme José Pimentel Lopes [UNESP]; Sampaio, José Eduardo Cezar [UNESP]; Marcantonio Júnior, Elcio [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (FapUNIFESP (SciELO), 2011)
This study used scanning electron microscopy (SEM) to evaluate the morphology and adhesion of blood components on root surfaces instrumented by curettes, piezoelectric ultrasonic scaler and Er,Cr:YSGG laser. One hundred samples from 25 teeth were divided into 5 groups: 1) Curettes; 2) Piezoelectric ultrasonic scaler; 3) Curettes plus piezoelectric ultrasonic scaler; 4) Er,Cr:YSGG laser; 5) Curettes plus Er,Cr:YSGG laser. Ten samples from each group were used for analysis of root morphology and the other 10 were used for analysis of adhesion of blood components on root surface. The results were analyzed statistically by the Kruskall-Wallis and Mann-Whitney tests with a significance level of 5%. The group treated with curettes showed smoother surfaces when compared to the groups were instrumented with piezoelectric ultrasonic scaler and the Er,Cr:YSGG laser. The surfaces instrumented with piezoelectric ultrasonic scaler and Er,Cr:YSGG laser, alone or in combination with hand scaling and root planing, did not differ significantly (p>0.05) among themselves. No statistically significant differences (p>0.05) among groups were found as to the adhesion of blood components on root surface. Ultrasonic instrumentation and Er,Cr:YSGG irradiation produced rougher root surfaces than the use of curettes, but there were no differences among treatments with respect to the adhesion of blood components.
Keywords: Dental scaling; Laser; Regeneration; Ultrasonic; fibrin; blood cell; cell adhesion; comparative study; cytology; dental surgery; dentin; human; instrumentation; low level laser therapy; methodology; periodontics; physiology; piezosurgery; preventive dentistry; radiation exposure; scanning electron microscopy; solid state laser; tooth root; ultrastructure; Blood Cells; Cell Adhesion; Dental Scaling; Dentin; Fibrin; Humans; Laser Therapy, Low-Level; Lasers, Solid-State; Microscopy, Electron, Scanning; Piezosurgery; Root Planing; Smear Layer; Subgingival Curettage; Tooth Root